ANALISIS RASIO LIKUIDITAS DAN SOLVABILITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT ADHI KARYA (PERSERO) TBK PERIODE 2016-2023 - Muhammad Kaffabian Latief; Syafrizal (Journal of Research and Publication Innovation, 2025)
This research aims to determine the financial performance of PT Adhi Karya (Persero) Tbk for the 2016-2023 period in terms of liquidity ratios and solvency ratios. The method used in this research is a quantitative method with a descriptive approach. The research data used is secondary data in the form of company financial reports that have been published by the Indonesia Stock Exchange (BEI). The results of the analysis show that the measurement of PT Adhi Karya (Persero) Tbk's liquidity ratio for the 2016-2023 period shows an unhealthy condition, because the Current Ratio (CR), Quick Ratio (QR) and Cash Ratio (CR) values ​​are below industry standards. The results of measuring the Solvency Ratio at PT Adhi Karya (Persero) Tbk for the 2016-2023 period show an unhealthy condition because the Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) values ​​are still below industry standards. PT Adhi Karya (Persero) Tbk's financial performance is at the "unhealthy" assessment level in liquidity research. Because the company is unable to meet its short-term obligations. And likewise, its solvency ratio is at an "unhealthy" level. Because the company is unable to meet its long-term obligations. To further increase its level of liquidity and solvency, companies should reduce the amount of long-term debt and increase their assets.